PENGKAJIAN PENGEMBANGAN MODEL AGRIBISNIS JAGUNG PADA LAHAN KERING DI KABUPATEN CIAMIS - Bachrein, Saeful (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2008)
Study on the Development of Maize Agribusiness Model in Up Land in Ciamis Regency. This study was conducted at Margaharja Village, Sub-district, Ciamis Regency from January to December, 2007. The objectives of the study were: (1) to design the formulation and development of agribusiness model system for village industry by implementing various technological and institutional innovations, and (2) to obtain feedback for the improvement of the model system and agribusiness activities as materials for program perfection. The activities were conducted by using "Before" and "After" approaches, and "Without" and "With" the introduction of technological and institutional innovations. The data observed comprise farm enterprise profile, the local technology performance compared with the technological innovations developed, business efficiency, the adoption of technological innovations, and institutional performance. Among the results of the study were: (1) The improvement of extension intensity and farmer group/ farmer group union dynamism showed by: (a) managing consolidation under the management of k farmer group/ farmer group union; (b) regular farmer group/ farmer group union meetings; (c) Problems in the provision of agricultural product infrastructure and marketing the harvested corn can be solved by the collaboration of farmer group union CV Karya Mulya and PT Petro Kimia, Gresik; (d) the availability of agribusiness clinics with various latest dissemination facilities for agricultural technology innovations and adequate meeting room; and (e) the availability if dissemination materials such as leaflets, technical guidelines, posters, scientific publications, and visual aids; and (2) From the technological exhibition it was obvious that supreme maize varieties , especially Sukmaraga, was demanded by most of farmers, hence they will be implemented widely in the 2007/2008 wet season. However, the planting of Sukmaraga variety cannot be realized by farmers as the seeds were not available when required. Key words: Agribusiness, village industry, technological innovations, and institutional innovations Pengkajian pengembangan model agribisnis jagung di lahan kering telah dilaksanakan di Desa Margaharja, Kecamatan Sukadana, Kabupaten Ciamis pada bulan Januari hingga Desember, 2007. Tujuan dari pengkajian ini adalah: (1) Merancang pembentukan dan pengembangan percontohan/model sistem agribisnis berbasis industri pedesaan melalui penerapan berbagai inovasi teknologi dan kelembagaan, dan (2) Mendapatkan umpan balik perbaikan model percontohan sistem dan usaha agribisnis sebagai bahan penyempurnaan program. Kegiatan ini dilaksanakan dengan menggunakan pendekatan "Sebelum" dan "Sesudah", serta "Tanpa" dan "Dengan" introduksi inovasi teknologi dan kelembagaan. Data yang diamati meliputi profil usahatani, kinerja teknologi setempat dibandingkan dengan inovasi teknologi yang dikembangkan, efisiensi usaha, adopsi inovasi teknologi, dan kinerja kelembagaan. Basil pengkajian, antara lain: (1) Peningkatan intensitas penyuluhan dan dinamika kelompoktani/gapoktan yang ditunjukkan, antara lain: (a) konsolidasi pengelolaan di bawah manajemen kelompoktani/gapoktan; (b) pertemuan kelompoktani/ gapoktan secara berkala; (c) Permasalahan dalam penyediaan sarana produksi pertanian dan pemasaran hasil panen jagung dapat teratasi melalui kemitraan gapoktan dengan CV Karya Mulya dan PT Petro Kimia, Gresik; (d) ketersediaan klinik agribisnis dengan Pengkajian Pengembangan Model Agribisnis Jagung pada Lahan Kering di Kabupaten Ciamis (Saeful Bachrein)berbagai fasilitas diseminasi inovasi teknologi pertanian terkini dan ruang pertemuan yang memadai; dan (e) ketersediaan materi diseminasi seperti leaflet, petunjuk teknis, poster, publikasi ilmiah, dan bahan peraga; dan (2) Dari basil gelar teknologi ternyata varietas unggul jagung, khususnya varietas Sukmaraga, sangat diminati sebagian besar petani sehingga akan diimplementasikan secara luas pada MH 2007/2008. Namun demikian, penanaman secara luas jagung varietas Sukmaraga tersebut tidak dapat dilaksanakan oleh petani karena benih tidak tersedia pada saat diperlukan. Kata kunci: Agribisnis, industri pedesaan, Inovasi teknologi, dan inovasi kelembagaan